Reassociation of Deoxyribonucleic Acids from Actinoplanes and Other Actinomycetes - Farina, Gandolfina (1970)
The ability of deoxyribonucleic acid (DNA) isolated from a number of actinomycetes to reassociate with reference DNA from Actinoplanes philippinensis or Streptomyces venezuelae has been measured. All of the DNA preparations except for those from Nocardia erythropolis and Thermomonospora viridis contained 70 to 73 moles per cent guanine and cytosine. DNA from two species of Actinoplanes, two species of Dactylosporangium, and Ampullariella digitata formed extensive thermally stable duplexes with the Actinoplanes philippinensis reference. DNA from streptomycetes formed duplexes with the A. philippinensis reference, but these duplexes possessed low thermal stability. DNA from N. erythropolis and T. viridis did not bind significant amounts of this reference DNA. Only DNA from Streptomyces albus, Streptoverticillium baldaccii, and Microellobosporia flavea appreciably bound the Streptomyces venezuelae reference. Our results separate the actinomycetes forming sporangia into two groups: the first group contained Actinoplanes, Dactylosporangium, and Ampullariella; the second group contained Planomonospora, Spirillospora, and Streptosporangium.